Sensitivity improvement of a new structure crack meter with angular adjustment. (November 2019) - Hong, Li; Wang, Jiahui; Yao, Zhenjing
In order to enhance the sensitivity improvement of crack meter in ruins rescue site, this paper proposes a novel crack meter with a V-shape structure. The mathematical analysis showed that there is a negative correlation between sensitivity of proposed crack and angle of V-shape structure. The finite element analysis using the ANSYS Workbench illustrates that sensitivity of proposed crack meter has rapid reduce with angle of V-shape structure of 14°–28°. Experimental findings show that the proposed V-shape structure crack meter has a higher sensitivity than the traditional one. With 14° V-shape structure crack meter, the sensitivity was enhanced to 1.16 mV/(mm/V), with an increase of 2.3 times over the traditional crack meter sensitivity of 0.35 mV/(mm/V).